Is Regional Economic Research Still Relevant?: A Bibliometric Approach Using Vosviewer - Aliyuddin, Muhammad (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2023)
This research aims to find out about the latest trends in regional economic research topics. The research method used in this research is bibliometric analysis using the Voswiewer application. Bibliometric research method is a research method that can analyze a very large volume of research. The bibliometric techniques used in this research are performance analysis and science mapping. The results showed that the most productive and most influential journals in regional economic research topics are journals affiliated with environmental science. The most influential researchers in the field of regional economics are dominated by researchers affiliated with universities from China. Based on science mapping analysis, it can be seen that there are three most dominant elements in regional economic topics, namely environmental regulation, covid, and urban agglomeration. Meanwhile, based on network visualization analysis, it is known that there are several recent topics in the field of regional economics, namely economic resilience, industrial agglomeration, and digital economy.Penelitian ini bertujuan untuk mengetahui mengenai perkembangan terbaru dalam topik penelitian ekonomi regional. Metode penelitian yang digunakan dalam penelitian ini adalah analisis bibliometrik dengan menggunakan aplikasi Vosviewer. Metode penelitian bibliometrik yaitu metode penelitian yang dapat menganalisis volume penelitian yang sangat besar. Teknik bibliometrik yang digunakan dalam penelitian ini yaitu performance analysis dan science mapping. Hasil penelitian menunjukan bahwa jurnal paling produktif dan paling berpengaruh dalam topik penelitian ekonomi regional merupakan jurnal – jurnal yang terafiliasi dengan bidang ilmu lingkungan. Peneliti paling berpengaruh dalam bidang ekonomi regional di dominasi oleh para peneliti yang terafiliasi dengan universitas dari negara China. Berdasarkan analisis science mapping dapat diketahui terdapat tiga elemen paling dominan dalam topik ekonomi regional yaitu environmental regulation, covid, dan urban agglomeration. Sementara itu, berdasarkan analisis network visualization diketahui terdapat beberapa topik terbaru dalam bidang ekonomi regional yaitu economic resilience, industrial agglomeration, dan digital economy.